ANALYSIS OF JUNIOR HIGH SCHOOL STUDENTS' MATHEMATICAL PROBLEM-SOLVING SKILLS IN HOTS TASKS BASED ON TOLAKI MEKONGGA LOCAL WISDOM - Tang, Nur; Mashuri, Sufri; Hidayati, Ully (Universitas Sembilanbelas November Kolaka, 2025)
Mathematical problem-solving is a crucial competence that enables students to think critically and creatively in facing real-life challenges. However, mathematics learning often lacks meaningful connections to students’ cultural contexts. This study integrates local wisdom from the Tolaki Mekongga community as a culturally relevant approach to strengthen students’ understanding of mathematical concepts. The study aims to describe and analyze junior high school students’ mathematical problem-solving abilities through ethnomathematics-based problems derived from Tolaki Mekongga traditions. This research employed a descriptive qualitative design involving 32 eighth-grade students from SMP Negeri 2 Kolaka. Data were collected through problem-solving tests and interviews, then analyzed according to Polya’s four stages: understanding, planning, implementing, and reviewing the solution. The findings revealed that most students demonstrated moderate to high levels of problem-solving ability. High-ability students could relate mathematical concepts to local cultural contexts, while low-ability students struggled to interpret contextual information and apply appropriate strategies. The study concludes that incorporating problems based on local wisdom enhances students’ engagement and conceptual understanding. Integrating cultural contexts such as Tolaki Mekongga traditions can serve as an effective ethnomathematical approach for improving mathematical problem-solving skills and fostering culturally responsive mathematics learning.